Dairy investment options for poverty reduction for small-scale dairy farmers in Tanzania - Lyatuu, Eliamoni T.R.; Okeyo Mwai, Ally; Komwihangilo, Daniel M.; Omore, Amos O.; Msuta, G.; Kelya, Neema; Ojango, Julie M.K.; Gebreyohanes, Gebregziabher (2022)
The effect of an unproductive investment could be detrimental to the investor, especially when is a dairy farmer investor who depend on earnings and may distort the productivity effort if is not approached with caution. Anyone who wish to invest in dairy farming must choose wisely, think independently to avoid follow the crowd. Ideal investment decisions in dairy would starts by best choice of breeds, feeds availability, affordability and accessibility, knowledge in proper animal husbandry and proper handling and marketing of animal products. Most farmers in Tanzania who are in dairy farming invested with different objectives, such as for prestige, for family nutrition, for manure and sale of live calves, to mention a few. This study investigating dairy cow investment and how it affects poverty situation in the families. The results show that investment in the dairy sector is the key to reliable income and leaning pole to poverty reduction in the family. Therefore, choice in investment may affect income and reduce poverty in two folds if it is done in ideal situation.